Detection of Low Pathogenic Avian Influenza Virus Subtype H10N7 in Poultry and Environmental Water Samples During a Clinical Outbreak in Commercial Free-Range Layers, Netherlands 2017 - Germeraad, Evelien A.; Elbers, Armin R. W.; de Bruijn, Naomi D.; Heutink, Rene; van Voorst, Wendy; Hakze-van der Honing, Renate; Bergervoet, Saskia A.; Engelsma, Marc Y.; van der Poel, Wim H. M.; Beerens, Nancy (Frontiers in Veterinary Science, 2020)
Wild birds are the natural reservoir of the Avian influenza virus (AIV) and may transmit AIV to poultry via direct contact or indirectly through the environment. In the Netherlands, a clinically suspected free-range layer flock was reported to the veterinary authorities by the farmer. Increased mortality, a decreased feed intake, and a drop in egg production were observed. Subsequently, an infection with low pathogenic avian influenza virus was detected. This study describes the diagnostic procedures used for detection and subtyping of the virus. In addition to routine diagnostics, the potential of two different environmental diagnostic methods was investigated for detecting AIV in surface water. AIV was first detected using rRT-PCR and isolated from tracheal and cloacal swabs collected from the hens. The virus was subtyped as H10N7. Antibodies against the virus were detected in 28 of the 31 sera tested. An intravenous pathogenicity index (IVPI) experiment was performed, but no pathogenicity (IVPI=0) was observed. Post-mortem examination and histology confirmed the AIV infection. Multiple water samples were collected longitudinally from the free-range area and waterway near the farm. Both environmental diagnostic methods allowed the detection of the H10N7 virus, demonstrating the potential of these methods in detection of AIV. The described methods could be a useful additional procedure for AIV surveillance in water-rich areas with large concentrations of wild birds or in areas around poultry farms. In addition, these methods could be used as a tool to test if the environment or free-range area is virus-free again, at the end of an AIV epidemic.